KAJIAN TERHADAP TRADISI HUKUM WARIS MASYARAKAT ADAT TENGGER - Farisma Eka Avaria; Farrel Al Hafiz; Indah Novitasari Nasution; Kinanti Putri Purnomo; Mirna Fajar Rahmawati (Pojok Publisher, 2025)
This study aims to analyze and also find out about the inheritance law in the Tengger tribe, which has a unique inheritance law that is passed down from generation to generation. The method used for this study is by using the literature review method. The results of this study indicate that the Tengger tribe has a bilateral inheritance system by equating boys with girls. For children who look after and care for their parents until they die, they will be given an award in the form of